Isotope specific resolution recovery image reconstruction in high resolution PET imaging. Issue 5 (17th April 2014) - Kotasidis, Fotis A.; Angelis, Georgios I.; Anton‐Rodriguez, Jose; Matthews, Julian C.; Reader, Andrew J.; Zaidi, Habib
Abstract : Purpose: : Measuring and incorporating a scanner‐specific point spread function (PSF) within image reconstruction has been shown to improve spatial resolution in PET. However, due to the short half‐life of clinically used isotopes, other long‐lived isotopes not used in clinical practice are used to perform the PSF measurements. As such, non‐optimal PSF models that do not correspond to those needed for the data to be reconstructed are used within resolution modeling (RM) image reconstruction, usually underestimating the true PSF owing to the difference in positron range. In high resolution brain and preclinical imaging, this effect is of particular importance since the PSFs become more positron range limited and isotope‐specific PSFs can help maximize the performance benefit from using resolution recovery image reconstruction algorithms. Methods: : In this work, the authors used a printing technique to simultaneously measure multiple point sources on the High Resolution Research Tomograph (HRRT), and the authors demonstrated the feasibility of deriving isotope‐dependent system matrices from fluorine‐18 and carbon‐11 point sources. Furthermore, the authors evaluated the impact of incorporating them within RM image reconstruction, using carbon‐11 phantom and clinical datasets on the HRRT. Results: : The results obtained using these two isotopes illustrate that even small differences in positron range can result in different PSF maps, leading to further improvements in contrast recovery when used in image reconstruction. The difference is more pronounced in the centre of the field‐of‐view where the full width at half maximum (FWHM) from the positron range has a larger contribution to the overall FWHM compared to the edge where the parallax error dominates the overall FWHM. Conclusions: : Based on the proposed methodology, measured isotope‐specific and spatially variant PSFs can be reliably derived and used for improved spatial resolution and variance performance in resolution recovery image reconstruction. The benefits are expected to be more substantial for more energetic positron emitting isotopes such as Oxygen‐15 and Rubidium‐82.